Growth expectations, undue optimism, and short-run fluctuations - Zeno Enders; Michael Kleemann; Gernot J. Müller (Deutsche Bundesbank, 2017)
We assess whether "undue optimism" (Pigou) contributes to business cycle fluctuations. In our analysis, optimism (or pessimism) pertains to total factor productivity which determines economic activity in the long run. Optimism shocks are perceived changes in productivity which do not actually materialize. We develop a new strategy to identify optimism shocks in a VAR model. It is based on nowcast errors regarding current output growth, that is, the difference between actual growth and the real-time prediction of professional forecasters. We find that optimism shocks - in line with theory - generate a negative nowcast error, but simultaneously a positive short-run output response.
Keywords: E32; 330; undue optimism; optimism shocks; noise shocks; animal spirits; business cycles; nowcast errors; VAR